Implementasi Metode Akselerasi Baca Kitab dalam Meningkatkan Motivasi Belajar Siswa Maktuba Pondok Pesantren Mambaul Ulum Pamekasan - Abdur Rahman (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This research was conducted because of the background of the problems that occur in society today, ranging from violence, corruption, robbery, moral crises and others, this makes many parties highlight the role of education, meaning that events in society cannot be separated from the role of education. The formulation of the problem in this thesis is First, how is the Implementation of the Book Reading Acceleration Method in Improving Student Learning Motivation at Mambaul Ulum Islamic Boarding School Pamekasan, Second, How is the Implementation of the Book Reading Acceleration Method in Increasing Student Learning Motivation at Mambaul Ulum Islamic Boarding School Pamekasan, Third, what are the factors supporters and barriers to the Implementation of the Book Reading Acceleration Method in Improving Learning Motivation of Maktuba Students at Mambaul Ulum Islamic Boarding School Pamekasan. This type of research is a field research that collects primary data through interviews from the chairman of the board, Guru Maktuba PP. Mambaul Ulum Pamekasan, and the guardians of students Maktuba PP. Mambaul Ulum Pamekasan, while the secondary data was obtained from literature and Maktuba PP documents. Mambaul Ulum Pamekasan, after all the data was collected, it was further analyzed qualitatively and described in a descriptive form. The results of the study concluded that: 1). The accelerated method of reading the book showed satisfactory results, namely the embedded humanism and religious values. 2). While the things that supported were the policies of the chairman of the board, educators, school friends, family, facilities and infrastructure. schools, facilities and infrastructure and families.Â Penelitian ini dilakukan dengan latar belakang permasalahan yang ada di masyarakat saat ini seperti kekerasan, korupsi, perampokan, krisis moral dan lain-lain yang membuat banyak pihak menekankan peran pendidikan yaitu peristiwa sosial yang tidak dapat dipisahkan. tentang peran pendidikan. Rumusan masalah dari tesis ini adalah Pertama, bagaimana Implementasi Metode Akselerasi Baca Kitab Dalam Meningkatkan Motivasi Belajar Siswa Maktuba Pondok Pesantren Mambaul Ulum Pamekasan, Kedua, Bagaimana Implementasi Metode Akselerasi Baca Kitab Dalam Meningkatkan Motivasi Belajar Siswa Maktuba Pondok Pesantren Mambaul Ulum Pamekasan, Ketiga, apa faktor pendukung dan penghambat Implementasi Metode Akselerasi Baca Kitab Dalam Meningkatkan Motivasi Belajar Siswa Maktuba Pondok Pesantren Mambaul Ulum Pamekasan. Jenis penelitian ini adalah penelitian lapangan yang mengumpulkan data primer melalui wawancara dengan ketua panitia Guru Maktuba PP. Orang tua siswa dari Mambaul Ulum Pamekasa dan Maktuba PP. Mambaul Ulum Pamekasan, data sekunder dari literatur dan dokumen Maktuba PP. Setelah semua data dari Mambaul Ulum Pamekasan terkumpul, analisis dilanjutkan secara kualitatif dan dideskripsikan dalam bentuk deskriptif. Hasil penelitian menyimpulkan bahwa1). Metode percepatan membaca buku menunjukkan hasil yang memuaskan yaitu pengenalan nilai-nilai humanistik dan religius. 2). Faktor pendukung meliputi kebijakan presiden, guru, teman sekelas, keluarga, sarana dan prasarana, sedangkan faktor penghambat meliputi teman sekolah, sarana dan prasarana dan keluarga.